2012
DOI: 10.1097/igc.0b013e3182370f51
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Sparing Surgery for Early Cervical Cancer—Approach to Less Radical Surgery

Abstract: It is possible to select patients for a less radical fertility-sparing procedure through identification of measurable low-risk factors and thus reduce the morbidity caused by conventional RVT. The selection criteria should be stringent and applied within the setting of a cancer center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Fertilitysparing surgical options, such as laparoscopic (LRT), abdominal (ART) and vaginal radical trachelectomy (VRT) or simple trachelectomies with or without pelvic lymphadenectomy, have been reported. [2,3,4,5] A study of Schmeler et al showed that 60% of trachelectomy specimens did not contain residual invasive malignant disease, [6,7,8,9,10] which raises the question if less radical surgery is possible in some cases. Furthermore, trachelectomies have been associated with preterm deliveries (before 31 weeks) in about one third of the patients.…”
Section: Introductionmentioning
confidence: 97%
“…Fertilitysparing surgical options, such as laparoscopic (LRT), abdominal (ART) and vaginal radical trachelectomy (VRT) or simple trachelectomies with or without pelvic lymphadenectomy, have been reported. [2,3,4,5] A study of Schmeler et al showed that 60% of trachelectomy specimens did not contain residual invasive malignant disease, [6,7,8,9,10] which raises the question if less radical surgery is possible in some cases. Furthermore, trachelectomies have been associated with preterm deliveries (before 31 weeks) in about one third of the patients.…”
Section: Introductionmentioning
confidence: 97%
“…Cervical stenosis does not necessarily result in infertility, and may be avoidable, depending on the technique employed 6 24. The overall calculable infertility rate of 17.9% in motivated women is only marginally higher than in the general population,3 6 7 and this figure may have been affected by factors not applicable to this case, such as radiotherapy treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Rob et al advocate the use of prophylactic antibiotics during pregnancy to minimise this risk, as the only case of PROM in their study occurred when antibiotic prophylaxis was ignored 7. Other authors do not concur; infection was not listed as a complication in the other three studies where antibiotics were not administered and, in Rob et al 's case, there may have been other confounding factors that predisposed to a poorer outcome 5–7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the morbidity related to treatment was reduced and the potential for fertility increased in the group submitted to simple trachelectomy 32 .…”
Section: Laparoscopic Lymphadenectomy Laparoscopic Lymphadenectomy Lamentioning
confidence: 99%